Distribution of microplastics in soil and freshwater environments: Global analysis and framework for transport modeling. (1st April 2021) - Koutnik, Vera S.; Leonard, Jamie; Alkidim, Sarah; DePrima, Francesca J.; Ravi, Sujith; Hoek, Eric M.V.; Mohanty, Sanjay K.
Abstract: Microplastics are continuously released into the terrestrial environment from sources where they are used and produced. These microplastics accumulate in soils, sediments, and freshwater bodies, and some are conveyed via wind and water to the oceans. The concentration gradient between terrestrial inland and coastal regions, the factors that influence the concentration, and the fundamental transport processes that could dynamically affect the distribution of microplastics are unclear. We analyzed microplastic concentration reported in 196 studies from 49 countries or territories from all continents and found that microplastic concentrations in soils or sediments and surface water could vary by up to eight orders of magnitude. Mean microplastic concentrations in inland locations such as glacier (191 n L −1 ) and urban stormwater (55 n L −1 ) were up to two orders of magnitude greater than the concentrations in rivers (0.63 n L −1 ) that convey microplastics from inland locations to water bodies in terrestrial boundary such as estuaries (0.15 n L −1 ). However, only 20% of studies reported microplastics below 20 μm, indicating the concentration in these systems can change with the improvement of microplastic detection technology. Analysis of data from laboratory studies reveals that biodegradation can also reduce the concentration and size of deposited microplastics in the terrestrial environment. Fiber percentage was higher in the sediments in the coastal areas than the sediments in inland water bodies, indicating fibers are preferentially transported to the terrestrial boundary. Finally, we provide theoretical frameworks to predict microplastics transport and identify potential hotspots where microplastics may accumulate. Graphical abstract: Image 1 Highlights: Microplastic concentration in river and farmlands can vary up to 8 orders of magnitude. Concentration between inland and coastal areas decreases by a factor of 1000. Biodegradation of microplastics in long term can change the concentration. Fibers are preferentially transported and enriched in coastal areas. Transport modeling with non-spherical microplastics is lacking. Abstract : Global analysis of microplastics reveals the concentration gradient between inland locations to coastal areas, unexpected hotspots such as glaciers, and the effect of aspect ratio on microplastics transport.